Preparing Teachers of Art - Day, Michael, 1938-; National Art Education Association (s.l. : The J. Paul Getty Trust, 1997)
"Focuses on the essential role of the teacher for improving student learning and for implementing school reform"--Http://www.naea-reston.org/publications-list.html
Preface -- Acknowledgments -- Preparing teachers of art for the year 2000 and beyond / Michael Day -- Whence come we? What are we? Whither go we? Demographic analysis of art teacher preparation programs in the United States / Enid Zimmerman -- What are teachers taught? An analysis of curriculum components for art teacher preparation programs / Lynn Galbraith -- Certification and licensure requirements for art education: comparison of state systems / Margaret Klempay DiBlasio -- The National Board for Professional Teaching standards: implications for art teacher preparation / Mac Arthur Goodwin -- Effects of school culture on art teaching practices: implications for teacher preparation / Kellene N. Champlin -- Accomplishing change in the university: strategies for improving art teacher preparation / James Hutchens
Includes bibliographical references.
Keywords: Art -- Study and teaching -- United States; Art teachers -- Training of -- United States